Developing recombinant phospholipase D1 (rPLD1) toxoid from Iranian Hemiscorpius lepturus scorpion and its protective effects in BALB/c mice. (15th September 2018) - Safari Foroushani, Narges; Modarressi, Mohammad Hossein; Behdani, Mahdi; Torabi, Elham; Pooshang Bagheri, Kamran; Shahbazzadeh, Delavar
Abstract: Hemiscorpius lepturus (H. lepturus) is one of the most dangerous scorpions and the most medically important scorpion in Iran. The clinical signs of H. lepturus envenomation, including dermonecrosis, hematuria, renal failure and early death, are attributed to phospholipase D activity. This study was conducted to develop a novel recombinant phospholipase D1 (rPLD1) toxoid and investigate its immunogenicity and protective effects against the lethality of H. lepturus venom. The lethal protein recombinant phospholipase D1 was expressed from PLD H. lepturus venom gland. The rPLD1 toxin was converted into toxoid (the first toxoid of H. lepturus PLD) with a 0.25% concentration of formalin and stored for ten days at room temperature. In the toxicity test, the lethal activity of recombinant phospholipase D1 was fully inhibited. When it reached up to 3 times higher than the maximal effective concentration of the purified toxin (11.1 μg), rPLD1 toxoid was used. The sphingomyelinase activity was inhibited when up to 5.4 times of the LD100 of the purified toxin (20 μg), toxoid was used. It was then used to produce an antibody in BALB/c as an antigen and the mice were then challenged with rPLD1 toxin and the whole venom. The immunogenicity of rPLD1 toxoid was evaluated and the maximum titer of the raised antibodies was determined by ELISA assay. The optimum titer for anti-rPLD1 toxoid sera was obtained at the third intraperitoneal injection of rPLD1 toxoid, and a high titer was reached at the fourth injection in the mice. This toxoid increased the amount of antibodies and produced a protective antiserum against the whole venom of H. lepturus and rPLD1 toxin. The in-vivo test results showed that the mice were completely resistant against 200 times the LD100 of recombinant phospholipase D1 and the whole venom of H. lepturus . To conclude, rPLD1 can be used in toxoid form as an immunogen in the production of a new generation of neutralizing antibodies against the lethality and toxicity of H. lepturus whole venom. Highlights: A major toxic protein, Phospholipase D1 from the venom of H. lepturus scorpion was expressed in E. coli (rPLD1 toxin). Formalin used to convert rPLD1 toxin to toxoid that is highly immunogenic in mice. The rPLD1 toxoid has the ability to neutralize up to 200 LD100 of the scorpion whole venom. Results of this study provide a basis for development of putative antigenic vaccine against H. lepturus stings.